The politics of physical activity - Piggin, Joe (Routledge research in physical activity and health, 2019)
Defining 'politics' as contests over ideas, values and visions about what a physically active society could be, this book uses critical analysis to challenge accepted truths about physical activity and therefore opens up a pathway to more effective, and more socially just, physical activity policy. Critiquing global and national physical activity policies which are arguing for significant change to societies around the world, The Politics of Physical Activity presents empirical case studies to illustrate the political dimensions of advocating for physical activity promotion, including discussions of resourcing difficulties, conflicts of interest and opportunity costs. It explores physical activity as a multi-sectoral tool that is being applied to political ideas and policy goals as varied as education, sustainability and social cohesion, and asks what good physical activity really looks like. This is important and provocative reading for any student, researcher, practitioner or policy maker with an interest in physical activity, public health or public policy